EFEKTIFITAS TERAPI SELF HELP GROUP (SHG) TERHADAP TINGKAT STRES DIMASA LANSIA: Effectiveness of SHG (Self Help Group) Therapy on Stress Levels in The Elderly - Intan Munawaroh; Shulhan Arief Hidayat; Ossi Dwi Prasetio; Angga Miftakhul Nizar (Jurnal Penelitian, 2024)
The elderly group has very complex health problems, both physiological and psychological. Health problems experienced by the elderly include a gradual decline in physical and psychological function, which can cause stress. This research aims to determine the effectiveness of SHG therapy on stress levels in the elderly in Campurdarat Village. This research was a quasi-experimental pre-test and post-test with a control group design. The population in this study were all elderly people in the Campurdarat District Area The independent research variable is SHG therapy and the dependent variable is stress level. Analysis test was carried out using Wilcoxon signed-rank test. The results show that SHG therapy affects stress levels in the elderly, it obtained a significance value (p-value) of 0,000<0.05. This is proven by a decrease in stress levels before and after being given SHG therapy in the intervention group. Keywords: Elderly; SHG; Stress.